Clean oxidations by iodobenzene dichloride: Platinum(IV) complexes containing triphenylphosphine. (1st May 2018) - Belli Dell' Amico, Daniela; Fioco, David; Labella, Luca; Marchetti, Fabio; Samaritani, Simona
Graphical abstract: [PtCl2 (PPh3 )(L)] complexes were oxidized to the corresponding Pt(IV) species by PhICl2 in dry solvents. [PtCl4 (PPh3 )(L)] complexes, fully characterized, are stable in the solid state, but decompose in solutions containing some water. The dynamic behavior shown by trans -[PtCl4 (PPh3 )(NCMe)] in CD3 CN solution suggests its possible use as precursor in substitution reactions. Abstract: Neutral complexes with generic formula [PtCl2 (PPh3 )(L)] were efficiently oxidized to [PtCl4 (PPh3 )(L)] (L = dibenzylamine, p -toluidine, diethanolamine, pyridine and acetonitrile) using PhICl2 The anionic complex [TBA][PtCl3 (PPh3 )] (TBA = Tetrabutylammonium) was also oxidized to [TBA][PtCl5 (PPh3 )] with this method. The obtained products were fully characterized by 1 H, 13 C, 31 P and 195 Pt NMR, IR-ATR spectroscopy, elemental analysis and, for complexes cis -([PtCl4 (PPh3 )( p -toluidine)]·CHCl3 and trans -[PtCl4 (PPh3 )(NCCH3 )]·CH3 CN, also by single crystal X-ray diffraction.